A Detached Eclipsing Binary with a Period Shorter than 0.2 Days in a Triple System. (8th February 2019) - Zhang, Bin; Qian, S.-B.; Zhi, Q.-J.; Liu, N.-P.; Dong, A.-J.; Michel, R.; Zhu, L.-Y.; Li, K.; Zhang, J.; Wang, Q.-S.
Abstract: W UMa-type binary stars have an apparent short-period cutoff around 0.2 days. Close binaries with orbital periods shorter than this limit are very useful for understanding the formation and evolution of this type of binaries. 2MASS J11553339+3544399 (hereafter J1155) is a red-dwarf binary with a period of 0.199724 days. Multicolor ( V, R, R c, I, I c, W ) light curves (LCs) for the ultrashort-period eclipsing binary (EB) J1155 are presented and analyzed by using the Wilson-Devinney (W-D) code. We find that J1155 belongs to a rare group of detached red-dwarf EB with periods below the period limit of contact binaries (the other two are BW03 V38 and GSC 2314-0530). It has a high-mass ratio of 0.90. The primary component (the more massive and hotter star) is filling 90% of the critical Roche lobe, while the secondary one is filling about 84.8%. The masses and radii of the two components are estimated as M 1  = 0.475 ± 0.035 M ⊙, M 2  = 0.441 ± 0.044 M ⊙, R 1  = 0.516 ± 0.089 R ⊙, and R 2  = 0.491 ± 0.105 R ⊙, respectively. By analyzing all available times of light minimum, the orbital period changes of the binary system are investigated for the first time. We find that the ( O − C ) (observed-calculated) diagram shows a cyclic oscillation with an amplitude of 0.00326 days and a period about 9.84 years. This oscillation is explained as the light-travel time effect (LTTE) via the presence of a third body. The mass of the third component in the triple system is computed to be M 3  sin ( i ′) ∼ 0.127 M ⊙ . The orbital distance between the central binary and the tertiary component is about 4.0 au. It is possible that the third body and the magnetic braking may play important roles in the formation and evolution of J1155 by drawing angular momentum from the central system.